Fertigation and growth regulator on coffee seedling production in tubes - Coelho, Victor Peçanha de Miranda (2019)
The use of quality seedlings is important in establishing a productive coﬀee crop. However, the most widely used method to produce coﬀee seedlings is time consuming (6-12 months) and lacks new production technologies. This study aimed to assess the use of fertigation and a growth regulator in the production of coﬀee seedlings, in order to develop a system faster than the conventional method. For that, Topázio coﬀee cultivar seeds were pre-germinated and planted in tubes flled with substrate (composted pine bark), in a protected nursery. A randomized block design was used, in a 4 x 2 (fertigation levels x the use or not of growth regulator) factorial scheme, with four replications. Daily fertigation positively inﬂuenced all the growth variables evaluated. The foliar spraying of the growth regulator had little eﬀect on seedling growth. When compared to the conventional system described in the literature, the coﬀee seedling production system described here reduced, by around 60 days, the production time and enables a largescale production